2001
DOI: 10.1093/emboj/20.3.446
|View full text |Cite
|
Sign up to set email alerts
|

Hsp72 functions as a natural inhibitory protein of c-Jun N-terminal kinase

Abstract: Hsp72, a major inducible member of the heat shock protein family, can protect cells against many cellular stresses including heat shock. In our present study, we observed that pretreatment of NIH 3T3 cells with mild heat shock (43 degrees C for 20 min) suppressed UV-stimulated c-Jun N-terminal kinase 1 (JNK1) activity. Constitutively overexpressed Hsp72 also inhibited JNK1 activation in NIH 3T3 cells, whereas it did not affect either SEK1 or MEKK1 activity. Both in vitro binding and kinase studies indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
222
2
9

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(239 citation statements)
references
References 67 publications
6
222
2
9
Order By: Relevance
“…Accordingly, HSP70 depletion is shown to sensitize PRO cell-free extracts to caspase activation by cytochrome c. Several other molecular mechanisms have been involved in the antiapoptotic e ect of HSP70, including inhibition of c-Jun N-terminal kinase (JNK) that contributes to cell death under certain conditions (Mosser et al, 1997;Park et al, 2001); interaction with AIF to prevent caspase-independent cell death (Ravagnan et al, 2001); prevention of cytochrome c release from the mitochondrion and refolding of proteins cleaved by e ector caspases (Jaattela et al, 1998). One or several of these mechanisms may account for the increased in vivo cell death induced by HSP70 depletion in PRO colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, HSP70 depletion is shown to sensitize PRO cell-free extracts to caspase activation by cytochrome c. Several other molecular mechanisms have been involved in the antiapoptotic e ect of HSP70, including inhibition of c-Jun N-terminal kinase (JNK) that contributes to cell death under certain conditions (Mosser et al, 1997;Park et al, 2001); interaction with AIF to prevent caspase-independent cell death (Ravagnan et al, 2001); prevention of cytochrome c release from the mitochondrion and refolding of proteins cleaved by e ector caspases (Jaattela et al, 1998). One or several of these mechanisms may account for the increased in vivo cell death induced by HSP70 depletion in PRO colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another way in which Hsp may act to promote survival and prevent cell death is through suppression of other apoptotic signaling pathways. Several laboratories have provided evidence indicating that Hsp70 can inhibit JNK activity and thereby inhibit JNK-mediated apoptosis (Gabai et al, 1997(Gabai et al, , 2000bPark et al, 2001a). Two different mechanisms may contribute to this function.…”
Section: How Do Hsp Protect Cells Against Oxidative Damage?mentioning
confidence: 99%
“…Sherman and colleagues have suggested that Hsp70 reduces JNK activity by increasing the rate of its dephosphorylation (Meriin et al, 1999;Volloch et al, 2000;Gabai et al, 2000a). An alternative mechanism is suggested by studies of Park et al (2001a) who provided evidence that Hsp70 binds to JNK to prevent its phosphorylation by upstream kinases. Importantly, the chaperone function of Hsp was not required for this effect.…”
Section: How Do Hsp Protect Cells Against Oxidative Damage?mentioning
confidence: 99%
“…On the other hand, if HSP72 acts as a suppressor of signal transduction, its refolding activity may be dispensable. Interestingly, the HSP72 mutant lacking the ATPase domain retains the ability to inhibit JNK (45,59,63) and protects fibroblasts from heat-induced killing (34,54,59). Because this mutant is unable to refold heat-damaged proteins (while being able to bind to them) (34,54), it appears that, at least in certain cell types, the JNK-inhibiting activity of HSP72 is sufficient for protection from heat-induced cell death.…”
Section: Hsps Control Apoptotic Signaling Pathwaysmentioning
confidence: 99%